Bloom's taxonomy revisited in the age of Artificial Intelligence - Prof. Dr GHAZI AZIZ et al. (International Journal of Scientific Research and Innovative Studies, 2025)
Bloom's taxonomy, originally developed in 1956 by Benjamin Bloom and his colleagues, proposes a hierarchical classification of learning objectives ranging from simple memorisation to creation: remembering, understanding, applying, analysing, evaluating and creating. This structure However, the advent of generative artificial intelligence (GAI) embodied by tools such as ChatGPT, DALL·E, Gemini and Copilot is profoundly transforming the way these cognitive levels are mobilised and developed. In the era of GAI, revising Bloom's taxonomy is essential. The learner is no longer a mere receiver, but a co-creator of knowledge with the machine. AI facilitates the lower levels (memorisation and comprehension) through the automatic generation of summaries, examples and contextualised explanations. This frees up time for higher cognitive activities such as analysis, evaluation and creation, where humans retain a critical and ethical role.Generative AI tools can, for example, simulate complex situations, generate personalised case studies or offer adaptive feedback, thereby promoting differentiated and experiential teaching. However, this transformation is not without its challenges: risks of cognitive dependence, assisted plagiarism, loss of critical thinking, and the need for new digital skills. Thus, the "revisitation" of Bloom's taxonomy in the era of generative artificial intelligence is not about replacing it, but reinterpreting it. It calls for augmented pedagogy, where humans retain cognitive and ethical leadership, while AI acts as a catalyst for learning. The goal is no longer just to create knowledge, but to co-construct meaning in an intelligent, interactive and critical environment. Keywords: Bloom's taxonomy, generative artificial intelligence, cognitive learning, digital pedagogy, educational transformation, AI ethics, augmented education, pedagogical innovation. Received Date: October 20, 2024 Accepted Date: November 11, 2025 Published Date: December 01, 2025 Available Online at: https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/516